Rationally-designed logic integration of regulatory signals in mammalian cells - Leisner, Madeleine (2010)
Molecular-level information processing1,2, or computing, is essential for ‘smart’ in vivo nanosystems. Natural molecular computing, such as messenger RNA (mRNA) synthesis regulation by special proteins called transcription factors (TFs)3,4, may inspire engineered systems leading to the next generation of nanobiotechnological and nanomedical applications. Synthetic pathways5–15 have already implemented logical control of mRNA levels by certain TF combinations. Here we show an alternative approach toward general-purpose control of mRNA and protein levels by logic integration of transcription factor input signals in mammalian cells. The factors regulate synthetic genes coding for small regulatory RNAs – microRNAs – that in turn control mRNA of interest (i.e., output) via RNA interference pathway. Simple nature of these modular interactions allows in theory to implement any arbitrary logic relation between the TFs and the output16. We construct, test, and optimize increasingly complex circuits with up to three TF inputs, establishing a platform for in-vivo molecular computing.